Evaluation of left renal vein and IVC variations in MDCT examinations performed in patients with a preliminary diagnosis of renal calculi : Evaluation of left renal vein and IVC variations in MDCT - Yılmaz , Behice Kaniye; Diker , Mustafa; Aslan , Suayip; Atasoy , Bahar; Karahasanoglu, Ridvan; Gocgun , Nurdan; Ozdemir , Sevim; Turkay , Rustu (Journal of Surgery and Medicine, 2023)
Background/Aim: Left renal vein (LRV) and inferior vena cava (IVC) variations are not rare, an observation that is extremely important to understanding the presence of these structures before performing surgery. This study aimed to evaluate the type and frequency of IVC and LRV variations with multi-detector computer tomography (MDCT) in patients admitted with a preliminary diagnosis of renal calculi and to evaluate the relationship of these variations with renal calculi, renal cysts, and horseshoe kidneys. Methods: We retrospectively analyzed 1640 patients who underwent abdominal CT for suspicious renal calculi between January 2018 and December 2019. This retrospective cohort study consisted of 1604 patients after the exclusion criteria. Renal surgery and/or renal agenesis examinations without enough diagnostic quality due to motion artifacts were considered the exclusion criteria. Age, gender, presence and types of IVC and renal variations, and presence of renal calculi, renal cysts, and horseshoe kidney were recorded. The relationship between variation types and presence of renal calculi, renal cysts, and horseshoe kidneys was evaluated. Results: IVC and LRV variations were detected in 107 patients (6.7%). The prevalence of circumaortic LRV (CLRV) and retroaortic LRV (RLRV), left IVC, and double IVC in 65 patients was 4.1%, 2.4%, 0.1%, and 0.1%, respectively. Male gender predominance in both total and RLRV were found in the variations (P=0.033 and P=0.033, respectively). Urinary calculi were found in 1016 (63.3%) of the patients, kidney cysts in 247 (15.4%), and horseshoe kidneys in 10 (0.6%). No correlation between the presence of renal calculi, kidney cysts, and horseshoe kidney and the presence of variations in patients with LRV was found (P=0.433, P=0.215, and P=0.500, respectively). Conclusions: LRV and IVC variations are not uncommon. It is necessary to be informed about these variations before performing retroperitoneal surgery to prevent possible complications. LRV and IVC variations can be easily recognized in pre-diagnosed renal calculi on MDCT without the use of an intravenous contrast agent.